PERGESERAN MAKNA TRADISI TEMU MANTEN PADA PERKAWINAN ADAT JAWA DI DUSUN WONOSARI DESA TEBANG KACANG KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Ermawati, Eka; Chalimi, Ika Rahmatika; Firmansyah, Haris (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractMarriage is a form of sacred bond in unifying relationships,namely the relationshipbetween men and women and also a bond in uniting two different families.in Javanesetraditional it has a unique traditional, namely Temu Manten. This study aimed to describethe shift in the meaning of Temu Manten in Javanese traditional marriages in WonosariHamlest, Tebang Kacang Village, Sungai Raya District, Kubu Raya Regency. This studyused a qualitative method with a descriptive-ethnographic approach. Data collectiontechiques used were observation guidelines, interview guidelines, and documentationtools. The data analysis during collection, data presentation or data display, and drawingconclusions or verification. Validation data used were the source and techniquetriangulation. Based on research conducted by Temu Manten Tradition, starting from theprocession of the Bride and Groom, Balangan Gantal, Wiji Dadi, Sindur, Dulangan,Kacar-Kucur, and Sungkeman procession. There was a shift in meaning in bridalprocession, which originally used Kembar Mayang and now it does not use it. And in WijiDadi procession, which originally used Kembar Mayang and now it does not use it. Andin Wiji Dadi procession, where the groom"™s feet are washed by his family, now his wifewashes his feet. The conclusion in this study is that those who experience a shift inmeaning in the procession of the bride and groom which originally used KembarMayang, now does not use it. And in Wiji Dadi procession, the firsh one who washes thethe feed of the groom"™s family and now his feed are washed by his wife.Keywords: Tradition, Wedding, Java.